Review Aplikasi Access dengan Pendekatan Webqual 4.0 untuk Meningkatkan Kepuasan Pelanggan - Puspitasari, Mariana Diah; Iswanto, Ary Putra; Astuti, Septiana Widi; Wicaksono, Adi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT Kereta Api Indonesia (Persero) launched "Access by KAI," an updated version of their "KAI Access" train ticket booking app. This study assessed user satisfaction with the Access app using Webqual 4.0 dimensions: usability, information quality, and service interaction. Researchers surveyed 400 users, analyzing their responses descriptively. The findings indicate a very satisfied user base across all Webqual 4.0 dimensions. Information quality received the highest average score, followed by usability, and then service interaction. Overall customer satisfaction with the Access app was also very high, surpassing the scores of individual dimensions.